Asuhan Keperawatan Pada Pasien Gout Arthritis Dengan Ketidakpatuhan Diet Rendah Purin - Muazam Nurfai Hardiansyah; Agung Eko Hartanto; Heru Wiratmoko; Yustina Purwaningsih; Gandes Widya Hendrawati (Universitas Sultan Ageng Tirtayasa, 2026)
Gout Arthritis is an acid formed due to purine metabolism in the body. Purine comes from foods containing protein. To maintain uric acid levels within the normal range, individuals must improve compliance with a low-purine diet supported by Health Education. The purpose of this study was to determine how nursing care is provided to gout arthritis patients with low-purine diet non-compliance. The research design was descriptive qualitative with a case study approach. Nursing interventions focused on diet education using leaflet media which showed a significant increase in the level of patient diet compliance, namely the compliance score increased from 2 (non-compliant) to 10 (compliant) within 7 days and resulted in a decrease in uric acid levels from 8.9 mg/dl to 5 mg/dl. The provision of this research education confirms that structured health education and appropriate educational media can improve diet compliance and health outcomes in gout arthritis patients.